EFFICACY AND SAFETY OF 23-VALENT PNEUMOCOCCAL POLYSACCHARIDE VACCINE IN PATIENTS WITH RHEUMATOID ARTHRITIS - M. S. Naumtseva; B. S. Belov; G. M. Tarasova; D. E. Karateev; E. L. Luchikhina; Yu. V. Muravyev; E. N. Aleksandrova; A. A. Novikov (Klinicist)
Objective: to study the clinical efficacy, immunogenicity, and safety of a 23-valent pneumococcal vaccine in patients with rheumatoid arthritis (RA). Subjects and methods. The investigation enrolled 70 patients (55 women and 15 men) aged 23–70 years, including 40 patients with RA and 30 people without systemic inflammatory rheumatic diseases (a control group) who had a recent history of 2 and more cases of lower respiratory tract infections (bronchitis, pneumonia). When included, all the patients received anti-inflammatory therapy with methotrexate (MT) (n = 24), leflunomide (LEF) (n = 6), or MT + tumor necrosis factor-α (TNF-α) inhibitors (n = 10). A single 0.5-ml dose of the 23-valent pneumococcal vaccine Pneumo-23 (Sanofi Pasteur) was administered subcutaneously or intramuscularly during continuous MT or LEF therapy for the underlying disease or 3–4 weeks before the use of a TNF-α inhibitor. During control visits (1 and 3 months and 1 year after administration of the vaccine), the patients underwent physical examination and routine clinical and laboratory studies. Results. No clinical and radiological symptoms of pneumonia were recorded in any case during a 12-month follow-up. The RA and control groups showed a more than 2-fold increase in anti-pneumococcal antibody levels 1 year after vaccination. The vaccine was well tolerated by 50 patients. Sixteen patients were observed to have pain, cutaneous swelling and hyperemia and 4 had subfebrility. There were neither episodes of RA exacerbation nor new autoimmune disorders during the follow-up. Conclusion. The findings suggest that 23-valent pneumococcal vaccine shows a good clinical efficacy, adequate immunogenicity, and good tolerability in the patients with RA.